A short-form of team mindset scale: Using psychometric properties of the items - Kim, Mirim; Han, Soo Jeoung; Kim, JiYoon (Frontiers in Psychology, 2023)
As the importance of a team function in educational and industrial settings has been emphasized, practical knowledge on team mindsets can be useful. Previous studies extended the mindset concept of individuals to the team context and developed 48-item team mindset scale (TMS) (Han & Kim, 2020). However, the original TMS had an issue when using it with many other scales due to the length of the survey. Therefore, the present study tested the psychometric properties of 48 items under a variety of perspectives to suggest a shorter version of TMS measuring the perception of the team mindset and having the desirable characteristics. We examined the construct validity of the TMS with exploratory factor analysis (EFA) with target rotation in Study 1 and tested item-level psychometric properties of the TMS in Study 2 based on classical test theory (CTT) and item response theory (IRT). Based on the result, we suggested the short-form of TMS, an 8-item TMS with adequate psychometric characteristics.